Implementation of Identification of Critical Points for the Halalness of Vegetable Materials and Their Derivative Products from an Islamic Economic Perspective - Karmila, Yusri; Parakkasi, Idris; Muthiadin, Cut; Supatminingsih, Tuti (PT FORMOSA CENDEKIA GLOBAL, 2024)
The aim of this research is to determine the implementation of identifying critical points for halal vegetable materials and their derivative products and the implementation of identifying critical points for halal vegetable materials and their derivative products from an Islamic economic perspective. This research uses a literature review of various main references in halal certification criteria and knowledge about ingredients and processing processes for products originating from plants (plant based products). It is concluded that vegetable ingredients in the sharia specifically mention that nothing is haram, so vegetable ingredients (vegetables) are basically halal. However, if the product is processed using additional ingredients or processing aids that are not halal, then the product status can change to non-halal. Identification of critical points for vegetable ingredients can be analyzed using a decision tree to identify critical points for halal vegetable ingredients.